Investigations on the spread of the spiralling whitefly (Aleurodicus dispersus, Russell) and field evaluation of elite cassava populations for genetic resistance - Asiwe, J.; Dixon, A.; Jackai, L.E.N.; Nukenine, E. (2002)
Studies were conducted at the International Institute of Tropical Agriculture, (IITA) to study the incidence and spread of the Spiralling whitefly (SWF) (Aleurodicus dispersus) at the IITA campus in lbadan, Nigeria, and the response of some of IITA's elite cassava germplasm to infestation by this pest. A. dispersus was recorded only in the experimental areas planted with cassava and a few other host plants, or where there was heavy traffic of people and materials. Evapo-transpiration and temperature, influenced the severity of infestation of A. dispersus more than other weather factors. Intensity 01 infestation significantly decreased with distance from the source of infestation (or epicenter) [y = 2-391-0.264><; A' = 0.90, P<0.05]. The cassava cultivars tested showed a wide range 01 responses to infestation by this insect suggesting the presence of variable genetic resistance.